Design of Belt Conveyor for Sandblasting Material Handling System - Liwiryon Sudarso; Rudi Suhradi Rachmat (Journal of Mechanical Engineering and Mechatronics, 2020)
Screw conveyor is a material transfer equipment that is often used in various types of industries. However, the screw conveyor also has some disadvantages if it used in the blasting room serves to transport the steel grit which is the main material in the blasting process. This screw conveyor often suffers damage to the pillow block due to the inclusion of steel grit. Based on field conditions, the screw conveyor transport capacity is considered inefficient because some of the steel grit left in the gap between the screw and the curved steel plate and not get transported by screw conveyor. In order to overcome the problems, a belt conveyor is chosen to replace the screw conveyor. The method used in this final project firstly is identifying the problem of the existing screw conveyor and observing the screw conveyor data. Secondly, by using the screw conveyor data, the author makes a design of a belt conveyor as the replacement of the existing screw conveyor. As a result, the belt conveyor design has been created with a calculated capacity of 236.81 tons/hour, which is greater than the existing screw conveyor. and is designed not to be easily damaged due to the inclusion of steel grit as it happened in the screw conveyor. Keywords: Screw Conveyor, Belt Conveyor, Steel Grit, Blasting Room, Pillow Block, Capacity, Design